Challenges and opportunities in healthcare leadership : voices from the crowd in today's complex and interprofessional Healthcare Environment - Lampe, Angela M.; Costanzo, Cindy; Leggio, William J.; Guetterman, Timothy C. (Emerald Publishing Limited, 2022)
Leaders in healthcare today face many challenges ranging from managing interprofessional teams and teamwork, to payment reform, to tackling issues such as homelessness and the opioid crisis. Leaders have access to depth of information and resources to help them solve these complex and real-world problems. However, it is our belief that given the complexities of healthcare, there is value in sharing and learning from those who have first-hand experience with interprofessional leadership in healthcare.Challenges and Opportunities in Healthcare Leadership: Voices from the Crowd in Today's Complex and Interprofessional Healthcare Environment, is a volume in a book series titled, Contemporary Perspectives in Business Leadership. In this book, authors share their true, authentic reflections and professional stories describing the lived experience(s) of the author/leaders and how the experience changed the author/leaders' approach as an interprofessional leader. Each chapter includes a (1) story about the topic and the lived experience, (2) perspectives, and (3) lessons of the author(s). Additionally, scholarly commentary and discussion questions included within each chapter create opportunity for application to leadership theories and strategies as well as allow for reflection and further dialogue on the topic.The intended audience is broad, including faculty and students in institutions of higher education, interprofessional healthcare team leaders and members, and other healthcare stakeholders who have experience in interprofessional healthcare leadership. The book is applicable for leadership growth and development at a personal, group, or organizational level.
Includes index.
Keywords: Medical care -- Management.; Educational leadership.; Interprofessional education.; Medical -- Nursing -- Management & Leadership.; Nursing management and leadership.; elektronické knihy; electronic books